Juridical Review of the Circulation of E-Cigarettes (Vaporizers) Containing Addictive Substances Based on Law No. 36 of 2009 on Health - Atika Sunarto; Ronal Pranata Manullang; Mashita Margaretha Manurung (LEGAL BRIEF, 2022)
Smoking is one of the activities that are still carried out by individuals at all ages, from teenagers to adults. Many ways can be done in an effort to stop smoking, such as committing, replacing cigarettes by consuming sweets, diverting cigarettes with more useful activities. But now news is circulating about smokers who try to quit smoking using e-cigarettes. propylene glycol, and taste. e-cigarettes contain liquid nicotine, propylene glycol, and glycerin. If all the ingredients are heated the meal will produce nitrosamine compounds and those compounds can cause cancer. Therefore, consumer protection must be strictly enforced. Results of this study said that e-cigarettes and conventional cigarettes have the same danger to their users because they contain nicotine and addictive substances that are harmful to health.